The Cancer-Associated Antigens Sialyl Lewisa/x and Sda: Two Opposite Faces of Terminal Glycosylation - Fabio Dall’Olio (MDPI AG, 2021)
Terminal carbohydrate structures are particularly relevant in oncology because they can serve as cancer markers and alter the phenotype of cancer cells. The Sda antigen and the sialyl Lewisx and sialyl Lewisa (sLex and sLea) antigens are terminal structures whose biosynthesis is mutually exclusive. In this review, we describe the main features of the Sda antigen in cancer and its relationship with sLex/a antigens. Information was obtained from an extensive literature search and from The Cancer Genome Atlas (TCGA) public database. The Sda biosynthetic enzyme B4GALNT2 undergoes downregulation in colorectal (CRC) and stomach cancer, while it is ectopically expressed by a minority of breast cancer (BRCA) patients. High expression of B4GALNT2 is associated with better prognosis and a less malignant gene expression profile in CRC, while the opposite occurs in BRCA. The regulation of B4GALNT2 expression in CRC is multifactorial, involving gene methylation and miRNA expression. Forced expression of B4GALNT2 inhibited sLea/sLex and reduced malignancy and stemness in cells constitutively expressing sLex/a antigens. However, consistent effects were observed upon B4GALNT2 forced expression and in cells not expressing sLex/a antigens. Thus, B4GALNT2 and the Sda antigen exert a tumor-restraining activity in CRC and probably other gastrointestinal cancers, independently of sLex/a antigens.